We celebrate the International Women’s Day with red lipstick! An analysis of female Russian migrants in Norway and their stories about the International Women’s Day : En kamp om forståelsesformer - Wara, Tatiana (Septentrio Conference Series, 2019)
This article illustrates how we can understand the International Women’s Day as a cultural phenomenon that mobilizes emotions. We link historical, political and empirical stories about the International Women’s Day to illustrate how female Russian migrants living in Norway draw on these narratives to create a room of their own. Our participants use the International Women’s Day as an occasion to both confirm and resist what they conceive as the majority’s perceptions of them as a group (‘Russian women in Norway’) by expressing femininity not as variations of gender neutrality, but rather in a ‘Russian way’ with skirt, high heels, nice hair and red lipstick. In the same vain, the participants also resist as what they perceive as the Norwegian majority’s understandings of equality as sameness. The article thus shows how ideas about femininity and gender equality travel between individual experiences and collective (historical and political) narratives, and illustrates how female migrants, by creating a room of their own, may at the same time create (partial) belonging in the majority society.